2010
DOI: 10.1088/0954-3899/37/6/064028
|View full text |Cite
|
Sign up to set email alerts
|

On the robustness of surface vibrational modes: case studies in the Cd region

Abstract: Recent studies of the stable Cd isotopes, using inelastic neutron scattering, radioactive decay and nucleon-transfer reactions, have resulted in the need to fundamentally reassess the concept of low-energy vibrational modes in these isotopes. We present a synopsis of the nuclear physics that has led to this situation, followed by the present status of spectroscopy for and against vibrational modes in nuclei neighbouring the Cd isotopes. We continue with some details of the spectroscopic techniques used and exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
65
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 46 publications
3
65
1
Order By: Relevance
“…The model is further supported by the measurement of a small quadrupole moment, Q(2 + 1 ) = +0.05(12) b [6], and the collective B(E2) values [7,8]. However, the spherical vibrator model has faced challenges in recent years a e-mail: evitts@triumf.ca e.g., Garrett et al have suggested the breakdown of vibrational excitations in the Cd isotopes [9,10]. In the Cd case it seems that mixing with multi-quasiparticle intruder configurations are likely to play a significant role in the development of apparent collectivity in the ground-state structure.…”
Section: Introductionmentioning
confidence: 94%
“…The model is further supported by the measurement of a small quadrupole moment, Q(2 + 1 ) = +0.05(12) b [6], and the collective B(E2) values [7,8]. However, the spherical vibrator model has faced challenges in recent years a e-mail: evitts@triumf.ca e.g., Garrett et al have suggested the breakdown of vibrational excitations in the Cd isotopes [9,10]. In the Cd case it seems that mixing with multi-quasiparticle intruder configurations are likely to play a significant role in the development of apparent collectivity in the ground-state structure.…”
Section: Introductionmentioning
confidence: 94%
“…The spectral and electromagnetic evolution revealed in these isotopes permits a systematic study of their nuclear structure properties, which also have an impact on nuclear astrophysics [3][4][5][6][7][8][9]. A recent study of the I π = 11/2 − isomers in Cd isotopes [10] indicates that the quadrupole and magnetic moments (denoted by Q and µ, respectively) both vary roughly as linear functions of neutron number.…”
Section: Introductionmentioning
confidence: 99%
“…Several candidates in the 48 Cd and 46 Pd region have been proposed as good examples of spherical quadrupole shape vibrators. However, a recent program of systematic study of even-mass stable Cd isotopes concluded that these nuclei are very poorly described by vibrational models [1][2][3]. This conclusion was based upon lifetime measurements of excited states in 110,112,114 Cd [4][5][6] which allowed the determination of B(E2)s that were found to be inconsistent with model calculations.…”
Section: Introductionmentioning
confidence: 99%